Ciri-Ciri Pengurusan Sekolah Berkesan - Lan, Poh Chin (1998)
The purpose of this study was to identify the characteristics of effective school management in secondary schools, which were identified as schools that were excellent in academic achievement. The five elements that were focused in this study were instructional leadership, communication, parental and community involvement, staff development, monitoring and evaluation. A total of one hundred and sixty eight teachers from Grade A Secondary Schools in the Seremban district took part as respondents in this study. A set of questionnaire was administered to collect data from teachers regarding their perception on the five elements in school management. Data were analysed by using the descriptive statistics where frequency counts and percentages were used to present the data. The results showed those four elements: instructional leadership, communication, staff development, monitoring and evaluation are indicators of school management that contribute to the effectiveness of school management. However, the practice of parental and community involvement in the school and Parent-Teacher Associations activities are not so obvious in the schools.